2006
DOI: 10.1097/01.aids.0000226963.10342.f4
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human papillomavirus infection in the anus, penis and mouth in HIV-positive men

Abstract: Human papillomavirus (HPV) types are associated with squamous cell cancers. HIV infection is linked with a higher prevalence of anal HPV infection. It is important to assess whether HPV is present in other body parts involved in sexual practices to establish a cancer prevention program. A high prevalence of high-risk HPV types was present in the anus, penis and mouth (78, 36 and 30%, respectively) in a cohort of HIV-infected males (men who have sex with men and heterosexual), without evidence of pathology in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 14 publications
10
42
2
2
Order By: Relevance
“…Nine of these 14 (64%) were found to have detectable anal HPV DNA, while seven of the 14 (50%) had an HR-HPV type detected, which probably represents persistence of infection. Larger international studies have reported a similar prevalence of HR-HPV infection, with persistence of HR-HPV infection in 50−70% of MSM and a higher persistence rate in HIV-infected subjects [21][22][23].HIV infection was positively associated with detection of HPV DNA (P = 0.04) and HR-HPV DNA (47% vs. 36% in HIV-negative individuals; P = 0.146) in our study. The high prevalence of HPV infection in HIV-infected subjects may be driven by an increased persistence of HPV infection as a consequence of compromised immunity and/or by a high incidence of new infections as a consequence of sexual behaviour.…”
supporting
confidence: 78%
“…Nine of these 14 (64%) were found to have detectable anal HPV DNA, while seven of the 14 (50%) had an HR-HPV type detected, which probably represents persistence of infection. Larger international studies have reported a similar prevalence of HR-HPV infection, with persistence of HR-HPV infection in 50−70% of MSM and a higher persistence rate in HIV-infected subjects [21][22][23].HIV infection was positively associated with detection of HPV DNA (P = 0.04) and HR-HPV DNA (47% vs. 36% in HIV-negative individuals; P = 0.146) in our study. The high prevalence of HPV infection in HIV-infected subjects may be driven by an increased persistence of HPV infection as a consequence of compromised immunity and/or by a high incidence of new infections as a consequence of sexual behaviour.…”
supporting
confidence: 78%
“…Anal cytology exams of our group of patients evidenced abnormalities in just 47.6% of the individuals with a lesion at anuscopy, and no HSIL was observed with cytology. The prevalence of abnormal cytology in HIV-positive men varies; whereas Moscicki et al and Wilkin et al found prevalence rates of 41.2% [9] and 48% [21], similar to what we found, Sirena et al reported 75% abnormal cytologies [30].…”
Section: Discussionsupporting
confidence: 90%
“…Sexual behavior apparently contributed to the high frequency of HPVmediated anal lesions in this group. These behaviors are among the main risk factors for acquisition of co-infection, namely receptive anal intercourse and a large number of sexual partners [11,20,[24][25][26][27]; this is the main route of transmission of HPV and HIV [3,24,25] and is an important risk factor for AIN [3,4,[28][29][30]. Surprisingly, 19% of the patients with an abnormal anal examination were heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of HIVinfected men, a high prevalence of high-risk HPV types (16 and 18) was found in the anus, penis and mouth (78%, 36% and 30%, respectively), without evidence of pathology in these areas. 82 The relative risk of penile cancer in HIV-positive patients is four times higher than that in HIV-negative men. 75 HIV-infected homosexual men have a substantially increased risk of HPV-induced anal cancer and anal intraepithelial neoplasia, and a moderately increased risk of penile cancer.…”
Section: Testicular Tumorsmentioning
confidence: 99%